Effect of Clinacanthus nutans leaf chloroform extract on reducing nitric oxide in fibroblasts - Erdita Hapsari; Rezky Anggraeni; Komariah Komariah; Moehamad Orliando Roeslan (Wolters Kluwer Medknow Publications, 2023)
Background: Clinacanthus nutans or dandang gendis is a plant that can be an effective herbal treatment for inflammation, in addition the Indonesian people are still looking for alternative treatments. Research shows that the antiinflammatory properties of C. nutans leaves are effective in reducing inflammation against fibroblasts. Nitric oxide (NO) is one of the inflammatory mediators, that are released by fibroblast when inflamed. Objective: To observe the effect of C. nutans leaf chloroform extract on reducing NO in inflamed fibroblasts. Methods: Fibroblasts stimulated with Escherichia coli lipopolysaccharide were treated with chloroform extracts of C. nutans leaves at concentrations of 25, 50, 100, and 200 μg/mL for 24 h, then a NO inhibition test was performed. Result: The C. nutans leaf extract at a concentration of 200 μg/mL resulted in significantly (P < 0.05) lower NO production than the negative control. Conclusion: C. nutans leaf chloroform extract has the effect of reducing NO in fibroblasts. This extract has the potential as an antiinflammatory agent.